HUKUM JUAL BELI AYAM TIREN DALAM FIQH MUAMALAT - Al Hafidz Ibnu Qayyim (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2020)
The Law of Buying and Selling Tiren Chicken in Muqalat Fiqh. The purpose of this study is to provide an explanation to the public regarding the law of buying and selling carcasses of tiren chicken according to the muamalat fiqh. Buying and selling carcasses of chicken chickens is forbidden if the purpose is to be consumed, but if it is for use other than for human consumption, such as fertilizer or for pet food such as cats and / or tigers, then the law may be noted that the government or the party that has the authority must closely monitor it. This is based on the Prophet's hadith. From Abdullah bin Abbas: Once passed in the presence of Rasulullah saw carcass of goat (to be thrown), then he asked: "Why is the skin not utilized?" They answered that the goat was a carcass. " Then the Messenger of Allah. also said that what is forbidden is just to eat it "(Narrated by Bukhari Muslim). With the completion of the legal research on the sale and purchase of these carcasses of chicken carcasses, hopefully the community can take advantage of the tiren chicken and of course have to be careful in its use.